Plasmonic Cu/CuCl/Cu2S/Ag and Cu/CuCl/Cu2S/Au supports with peroxidase-like activity: Insights from surface enhanced raman spectroscopy - Song, Wei; Hildebrandt, Peter; Weidinger, Inez M. (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2018)
In the present study, we present nanostructured bimetallic Cu/CuCl/Cu2S/Au(Ag) supports that exhibit plasmonic electromagnetic field enhancement and peroxidase-like catalytic activity. The Cu2S component acts as the peroxidase-like catalyst, while the Au or Ag component provides the necessary light enhancement for surface enhanced Raman spectroscopic (SERS) studies of surface bound molecular reactants. As a test reaction the catalytic oxidation of 3,3′,5,5′-tetramethylbenzidine (TMB) in presence of H2O2 was investigated. The comparison of product evolution in solution measured by UV-Vis spectroscopy and on the surface measured via SERS is able to give more insight into the different steps involved in the overall catalysis.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Ag; Au; Cu; peroxidase-like catalytic oxidation; SERS